Growth strategy of microbes on mixed carbon sources - Xin Wang (Nature Portfolio, 2019)
Bacteria grown on two carbon sources either consume both sources simultaneously or consume them sequentially. Here the authors use a metabolic network model of E. coli to show that optimal protein resource allocation and topological features of the network can explain the choice of carbon acquisition.